Dixie Cox Marie in western wear - Sahl, Ted (photographer):::Creator::::::::::::
Close-up view of Dixie Cox Marie smoking a cigar. She is wearing western gear, a black cowboy hat, gloves, and a large belt buckle and gun holster are visible.